Antibodies to Domain 4/5 (Dm4/5) of β2-Glycoprotein 1 (β2GP1) in different antiphospholipid (aPL) antibody profiles. Issue 1 (July 2015) - Pengo, V.; Ruffatti, A.; Tonello, M.; Hoxha, A.; Bison, E.; Denas, G.; Padayattil Jose, S.; Zoppellaro, G.; Bracco, A.; Banzato, A.
Abstract: Background: Determination of the three recommended tests for the diagnosis of antiphospholipid syndrome [Lupus Anticoagulant (LA), anticardiolipin (aCL) and anti β2-Glycoprotein 1 (aβ2GP1) antibodies] allow physicians to allocate patients into classification (risk) categories. Objectives: To measure antibodies of IgG isotype directed towards Domain 4/5 (Dm4/5) of β2GP1. Patients/Methods. In this cross-sectional study we measured IgG aβ2GP1-Dm4/5 in a group of individuals positive for IgG aβ2GP1 and classified as triple (LAC +, IgG aCL +, IgG aβ2GP1 +, n = 32), double (LAC-, IgG aCL +, IgG aβ2GP1 +, n = 23) or single positive (LA-, IgG aCL-, IgG aβ2GP1 +, n = 10). Results: Geometric mean and standard deviation of IgG aβ2GP1 values expressed as Chemiluminescent Units (CU) in triple, double, single positive groups and in 40 healthy individuals were 1795 ± 783, 321 ± 181, 29 ± 8 and 5.0 ± 1.0, respectively (ANOVA p < 0.0001). Geometric mean and standard deviation of IgG aβ2GP1-Dm4/5 expressed as Optical Density (OD) in triple, double and single positive groups and in 40 healthy individuals were 0.16 ± 0.13, 0.16 ± 0.15 and 0.26 ± 0.15, 0.13 ± 0, 11, respectively (ANOVA p < 0.002). Individuals in the single positive group, expressed significantly higher values with respect to triple (p = 0.04) and double (p = 0.03) positive groups. Approximate OD cut-off value (99° percentile) calculated in 40 normal control subjects is 0.404. Positivity to IgG aβ2GP1-Dm4/5 according to this cutoff was found in only 5 individuals, 3 in triple positive and 2 in single positive groups and was not associated with thromboembolism. Conclusion: Mean level of IgG aβ2GP1-Dm4/5 is higher in single positive group. There is no association between positivity to IgG aβ2GP1-Dm4/5 and thromboembolic events. Highlights: aβ2GP1 is a lab criterion in antiphospholipid syndrome aβ2GP1 comprises antibodies directed to different domains of the molecule Higher values of IgG aβ2GP1-Dm4/5 in patients with sole positivity for IgG aβ2GP1 No association between positivity to IgG aβ2GP1-Dm4/5 and thromboembolic events